IMPLEMENTASI PERATURAN DAERAH KABUPATEN BANYUWANGI NO 02 TAHUN 2020 TENTANG PENANGGULANGAN KEMISKINAN - Febri Yusdianatari, Wanda; Wilujeng, Sri; Jatu Permatasari, Safrieta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2025)
The high poverty rate in Rejosari Village, where many people lack the skills to develop micro-enterprises.The research objective aims to evaluate the effectiveness of the micro-enterprise skills training program in improving community welfare.The research methodology uses a qualitative approach with purposive sampling and snowball sampling techniques to determine informants.Data collection was carried out through interviews, observations, and documentation.The research results show that the skills training program has been running well, but there are still obstacles in terms of understanding and community participation.The discussion reveals that effective communication between the village government and the community is crucial for increasing participation in the program.Adequate human resources and facilities also play a role in the successful implementation of policies.The conclusion of this study emphasizes that although there has been progress in the implementation of the program, further efforts are still needed to raise public awareness and ensure the sustainability of the training program.